Upaya Peningkatan Keamanan Warga Melalui Optimalisasi Penerangan Jalan di Nagari Tanjung Gadang - Armaita Armaita; Pipit Khofifah; Khusnil Hidayat Lubis; Muhammad Faras Dzikra; Louisa Ananta; Abdul Latif; Farhan Syukri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The phenomenon of the absence and lack of public street lighting (PJU) as well as navigation facilities such as convex mirrors has become a significant challenge in ensuring driving safety in rural areas. Nagari Tanjung Gadang, Lareh Sago Halaban District, Lima Puluh Kota Regency, experiences a similar issue that impacts the increased risk of traffic accidents. This community service was carried out in the form of a Student Study Service (KKN) activity on February 3, 2026, with the aim of improving citizen safety through the optimization of street lighting and the installation of convex mirrors. The implementation methods include participatory observation, identification of accident-prone points, technical planning, procurement of materials based on appropriate technology, physical installation through mutual cooperation (gotong royong), and continuous evaluation. The results of the activity indicate that the installation reflector units and convex mirrors units successfully increased the level of visibility in accident-prone locations, as well as fostered public awareness regarding the importance of road safety infrastructure. The real impact is reflected in the increased community participation in maintaining the facilities and the decreased potential risk of accidents in strategic locations.